THE EFFORTS OF TIMOR LESTE TO RESOLVE THE MARITIME BOUNDARY DISPUTES WITH AUSTRALIA IN 2016-2018 - Winda Trisen; Tri Joko Waluyo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This research explains the efforts of Timor Leste resolve the maritime boundary disputes with Australia. Perspective that used in this research is neorealism perspective. All countries in the international system are made functionally equal by structural pressure, This research also uses the track two diplomacy theory. This theory is assumed to be an extension of track one diplomacy, whose actors are non-government actors who are able to carry out diplomatic activities, analyze, prevent and resolve a international conflict.The results of this research can show that Timor Leste and Australia had succeeded reach an agreement on their maritime boundaries. The agreement resulted of Timor Leste’s efforts to resolved maritime boundary disputes with Australia under the Permanent Court of Arbitration (PCA) Conciliation based on Article 298 and Annex V of the United Nations Convention on the Law of the Sea (UNCLOS). Timor Leste signed their Maritime Boundary Agreement on 6 March 2018 at United Nations Headquarters, New York. The settlement of the maritime boundary resulted better deal than before and opened a new chapter for bilateral relations between Timor Leste and Australia. Keywords : Neorealism perspective, trck two diplomacy. Maritime boundary agreement, UNCLOS, PCA, Conciliation